Strategi guru dalam meningkatkan minat belajar siswa Sekolah Dasar Negeri Unggulan 1 Pulau Morotai - Millenia, Alivia Puttri Wisnu; Rahim, Abdul (Universitas Sarjanawiyata Tamansiswa, 2025)
The condition of the Covid-19 pandemic in the world has had a huge impact on various sectors of life, including education. Learning in schools has changed from face-to-face to online. All stakeholders are required to be able to adapt to this change. SD N 1 Morotai is one of the schools that carries out online learning. However, the school admits that online learning encounters various obstacles, such as: gadgets, laptops, internet networks, and students' interest in participating in online learning. Based on this, this research will describe teachers' strategies for increasing students' online interest in learning during the Covid-19 pandemic at SD 1 Morotai. The data in this research will be processed qualitatively using descriptive methods. Data collection methods use observation, interview and documentation techniques. The research results show that teachers' strategies for increasing students' interest in learning during the Covid-19 pandemic online at SD N 1 Morotai are: (a) The teaching materials implemented by teachers in increasing students' interest in learning are by compiling teaching materials that contain information about learning materials in the form of documents that can be downloaded on students' learning devices. (b) The learning media implemented by teachers in increasing students' online interest in learning during the Covid-19 pandemic are Google Meet media as a virtual class, WA groups as a means of joint communication, and PPT for delivering learning material.